Derivation of completely cell culture-derived mice from early-passage embryonic stem cells. - Nagy, A (1993)
Several newly generated mouse embryonic stem (ES) cell lines were tested for their ability to produce completely ES cell-derived mice at early passage numbers by ES cell <==> tetraploid embryo aggregation. One line, designated R1, produced live offspring which were completely ES cell-derived as judged by isoenzyme analysis and coat color. These cell culture-derived animals were normal, viable, and fertile. However, prolonged in vitro culture negatively affected this initial totipotency of R1, and after passage 14, ES cell-derived newborns died at birth. However, one of the five subclones (R1-S3) derived from single cells at passage 12 retained the original totipotency and gave rise to viable, completely ES cell-derived animals. The total in vitro culture time of the sublines at the time of testing was equivalent to passage 24 of the original line. Fully potent early passage R1 cells and the R1-S3 subclone should be very useful not only for ES cell-based genetic manipulations but also in defining optimal in vitro culture conditions for retaining the initial totipotency of ES cells.